CURRENT STATUS AND PROSPECTS OF FREEDOM SQUARE CITY OF KHARKIV - , Н. Я., М. А. (Municipal economy of cities. Series: «Economy science», 2013)
The features of the formation of the architectural environment Freedom Square in Kharkov in the course of its evolution.